My children! my Africa! - Fugard, Athol (Theatre Communications Group, Inc., 1989)
"Generational conflict over the most effective means for ending apartheid in South Africa lead to an explosive confrontation between a gifted but impatient black township youth and his devoted but "old fashioned" black teacher... The unexpected involvement of a young white woman who befriends and learns from both men strips away the political trappings to reveal the human trauma at the heart of South Africa's... tragedy."--From publisher description.